Peningkatan Pengetahuan Pengurus Desa Tentang Program Poskesdes Promotif, Preventif, Kuratif dan Rehabilitatif - Andi, Muhammad Alwi (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2023)
The Desa Siaga approach includes efforts to bring basic health services closer to village communities, prepare the community to face health problems, orient the community in developing clean and healthy living behavior. Desa Siaga is a picture of a society that is aware, willing and able to prevent and overcome various threats to public health. The aim of this community service is to increase village administrators' knowledge about promotive, preventive, curative and rehabilitative village health post programs. This community service was carried out on August 25 2023 using the lecture method where the 16 participants who were Gerimak Indah village administrators were given an explanation of the aims and benefits of the community service carried out. Participants were given a questionnaire sheet regarding knowledge about promotive, preventive, curative and rehabilitative health post programs before and after education. The results of community service activities that have been carried out in Gerimak Indah Village show that there is a difference in knowledge before and after education where knowledge results have increased.